Assessment of Satisfaction with the Quality of Conventional Treatment in Patients with Diagnosed Civilisation Diseases in the Contex of Professional Nurse Competences - Ogórek-Tęcza, Ogórek-Tęcza; Zachara, Natalia (Nursing in the 21st Century, 2015)
ASSESSMENT OF SATISFACTION WITH THE QUALITY OF CONVENTIONAL TREATMENT IN PATIENTS WITH DIAGNOSED CIVILISATION DISEASES IN THE CONTEX OF PROFESSIONAL NURSE COMPETENCESIntroduction. Satisfaction with the quality of conventional treatment, including nursing care, in the opinion of patients directly translates into levels of satisfaction, whose quantifiable indicators provide information on quality within the healthcare system. Medical team is required to perform their professional duties with best possible results, which becomes particularly meaningful with respect to patients who suffer from cardiovascular diseases, as they have become an increasingly pressing health issue among the senior population.Aim. Assessment of competences and evaluation of quality of conventional care among the patients treated for cardiovascular diseases.Material and methods. Research covered a group of 100 patients hospitalized due to ischemic heart disease and arterial hypertension. Author`s questionnaire was used as research tool with the support of anonymous Questionnaire of Patient Satisfaction (QPS).Results. The patients taking part in the evaluation and assessing the level of medical care as high accounted for 74%. A significant group (77%) expressed satisfaction with treatment or care procedures they underwent. Similarly, a large group of participants (76%) underlined the fact of receiving the information related to their functioning with the disease. Just as highly patients evaluated the level of cooperation (66%) with the medical team and their promptness in bringing help (60%). A statistically significant correlation between the age of the patients and the level of satisfaction with medical care was noted.Conclusion. In the opinion of evaluated patients, the general assessment of the quality of care was highly positive. Men and persons from the age group of 66-85 gave a higher assessment of quality of performed medical services. General nursing competences in the educational scope were assessed as being average. Patients with higher education and persons from the age group of 26-45 years of age were harsher critics, more demanding with respect to nurses’ competences.